Exploring the Types of Casinos Preferred in Japan via Conjoint Analysis of Relevant Words. (1st January 2019) - Komiya, Nozomi; Nakamura, Jun
Abstract : A word can carry different meanings for different people. Conjoint analysis was applied to assess preferences for various words describing integrated resorts (IR) including casinos, to be introduced in Japan in the future. We discuss how the participants understood particular words (e.g., a specific casino's place name or wording regarding restrictions on betting) that define the characteristics of a casino, as well as how casino-related words influenced participants' preferences. Implications for enhancing public understanding of casinos are explored in the conclusion.